Successful Credit Control in a Week - Mason, Roger (London Hodder & Stoughton, 1999)
In the SUCCESSFUL BUSINESS IN A WEEK series, a guide to the basics of credit control, including precautions to take when opening accounts, telephone skills and overcoming excuses, as well as using the courts and legal system. It is illustrated with cartoons and is written by the author of FINANCE FOR NON-FINANCIAL MANAGERS IN A WEEK.
Includes Illustrations
Institute of Management
Keywords: Credit -- Management